Fragrance Product Quality Improvement Assistance In the Creative Home Industry - Muhammad Ramadhana Alfaris (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
This home creative industry is a new entrepreneur which makes deo active (deodorizer) in Pisang Candi village, Malang city. Trying to make simple and useful products by using simple equipment. Therefore it is necessary to be improved from the aspect of knowledge and skill, so that resulting in a quality fragrance product and able to compete in the market. The problems experienced by this partner are quite significant, such as packaging and label design that is less interesting, and then do not yet understand information technology to increase sales of fragrance product. the purpose of this program to improve product quality of fragrance product (deo active) like a deodorizer in Pisang Candi Village, Malang City. The method in this program is carried out comprehensively which is able to inventory the development of mindset in entrepreneurship, provide business facilities and equipment, and marketing through mentoring programs. The results of this program are partner products get better after being designed, the marketing process becomes more effective when through an online marketing system using e-commerce platforms in Indonesia so that increasing sales turnover of product.